Daily meals in context: A quantitative analysis of elementary school students' drawings - Kinoshita, Luna; Goto, Aya; Okabe, Satoko; Satoh, Kenichi; Honda, Kaori; Ueda, Kimiko; Murakami, Michio; Nollet, Kenneth E. (Frontiers in Communication, 2023)
To investigate school-age children’s perspectives on food and nutrition, we pilot tested a method to quantify and analyze crayon drawings collected from students in health education classes at two elementary schools in Fukushima, Japan. Included were 28 students in a mixed class of first and second graders and 26 students in a fourth-grade class. Specific foods, general shapes, and color choices in children’s drawings were entered into a spreadsheet and analyzed quantitatively. From first- and second-graders’ data, co-occurrence network analysis put meals into three groups: at home, eating out, and lunch boxes. Among fourth graders, co-occurrence network analysis called attention to the cucumber, noteworthy for being a local agricultural product. In addition, students who drew more side dishes also drew more staple foods and main dishes (p=0.04), used more colors (p=0.006), and showed satisfaction with their community (p=0.04). These results suggest that students’ understanding of eating was centered on the places where they eat and that they valued regional specialty products. Furthermore, the drawing of side dishes was indicative of a balanced diet, which in turn was associated with higher satisfaction with their community. Our trial indicates that children’s drawings can be a useful tool for adults to grasp children’s understanding of health-related information in daily living.